PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING BERBANTUAN VIDEO ANIKUR (ANIMASI PENGUKURAN) DALAM MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA SEKOLAH DASAR - Destiar Putri Wulandhari, Ellysa; Zulmi Roestika Rini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics is one of the most important subjects in life because it can play a role in improving critical thinking skills and reasoning abilities. The purpose of this study is to determine the effect of the contextual teaching and learning (CTL) learning model assisted by anikur media. The researcher used a quantitative approach. The population in this study were all students of Candirejo 01 and Candirejo 02 Elementary Schools. The sample in this study was grade III of Candirejo 01 Elementary School as the experimental class, and grade III of Candirejo 02 Elementary School as the control class. The sample was taken purposively using a nonprobability sampling technique. Data collection techniques in this study were observation, questionnaires, and pretest and posttest questions. Data analysis techniques in this study were tests and regression tests. The results of the study showed that a significance value of 0.00 <0.05 indicated that Ho was rejected or H1 was accepted. The average of the control group differed from the average of the experimental group. In addition, based on the results of the regression test, a significance level of 0.002 was obtained. Therefore, the sig value <0.05 means that the above variables influence each other, with t count = 9.471 > t table = 0.647. Thus, it can be understood that third-grade students of Candirejo 01 and Candirejo 02 Elementary Schools with the implementation of the Contextual Teaching and Learning (CTL) learning model have a significant influence on students' reasoning abilities.